mnożenie wyrażen algebraicznych;
wykonaj mnożenia.oblixzenia przedstaw na grafie
a). (2a-b)(a-7b)(5-c)
b).(a-3)(b-1)(c+8)
c). -(a-1)(c-2)(b+3)
d).z(y-2)(3x-1)(y-4)



Odpowiedź :

a) =(2a²-14ab-ab+7b²)(5-c)=10a²-2a²c-70ab+14abc-5ab+5abc+35b²-7b²c=10a²-2a²c-75ab+19abc+35b²-7b²c
b) =(ab-a-3b+3)(c+8)=abc+8ab-ac-8a-3bc-24b+3c+24
C) =(-a+1)(c-2)(b+3)=(-ac+2a+c-2)(b+3)=-abc-3ac+2ab+6a+bc+3c-2c-6=-abc-3ac+2ab+6a+bc+c-6
d) =(zy-2z)(3x-1)(y-4)=(3xyz-zy-6xz+2z)(y-4)=3xy²z-12xyz-zy²+4yz-6xyz+24xz+2yz-8z=3xy²z-18xyz-zy²6yz+24xz
Zobacz obrazek Elcia77